EFEKTIVITAS KOMUNIAKASI ORGANISASI DALAM PELAKSANAAN FUNGSI HUMAS PADA KANTOR DPRD PROVINSI SULAWESI SELATAN - Ainun , Nurul; Ahdan, Ahdan; Idris, Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The aims of this study are (1) to determine the implementation of the Public Relations function of the DPRD of South Sulawesi Province. (2) To determine the effectiveness of organizational communication in the public relations of the DPRD of South Sulawesi Province. The method used in this research is qualitative method. There were four informants in this study. This research lasted for one month and was located at the DPRD Office of the South-Sulawesi Province. The research method used in this study is a qualitative method. Data collection techniques through observation, interviews and documentation. This research lasted for one month and took place at the South Sulawesi DPRD office. Based on the results of the study, it can be concluded that the Effectiveness of Organizational Communication in the Implementation of the Public Relations Function at the DPRD Office of the Province of South Sulawesi is effectively in accordance with the function of public relations, namely being trusted, supportive, open, paying attention, and actively asking for opinions, as well as giving awards for high performance standards. good. As well as in implementing the public relations function, the DPRD of South Sulawesi Province applies an online system and is very efficient to accommodate people's aspirations so that mutual communication occurs.